Investigation of the relationship between male young elite wrestlers' blood and salivary lactate densities through the application of non-invasive lactate threshold estimation method subsequent to the effectuation of stationary periodic wrestling-based - Mohammad Mohammadi; Sedigheh Sadat Hojjati (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2018)
The purpose of the present study was to scrutinize the relationship between male young and elite wrestlers' blood and salivary lactate densities and, heart rate through the non-invasive estimation of lactate threshold after the effectuation of a certain periodic wrestling-based exercise protocol. To this end, 20 male young elite wrestlers (Age 17 ± 2.5; Height: 178.73 ± 4.4; Weight: 65.2 ± 6.4; Fat percentage: 13.45 ± 1.2) were incorporated into the study. The subjects effectuated the periodic wrestling-based exercise protocol in 5 minute phases so that their heart rates could be recorded using a Polar heart rate meter. The blood and salivary lactate sampling involved six phases including: resting mode, after warming up for 15 minutes and, after effectuation of four 5-minute exercise phases at intensities of 60%, 70%, 80% and, 90%. Blood and salivary lactate samples were taken during the passive 5-minute resting periods between the exercise phases. The data were analyzed through the application of the ANOVA test with repeated measurements and the Spearman correlation test at the significance level of 0.05. Considering the results, a statistically significant difference exists between the values of blood and salivary lactate between the aforementioned six phases. On the other hand, an acceptable correlation exists between the phase five's and the phase six's (at intensities of 80% and 90%) values of blood and salivary lactate (P<0.05, R5-69 & P<0.05, R6-59) while there are is also a high correlation evident between heart rate and lactate levels in phases number five and six (P<0.05, R5-59 & P<0.05, R6-63). Therefore the method of salivary lactate estimation could possibly be used as a non-invasive method in physiology studies for the objective determination of anaerobic threshold for such exercise protocols.   RESUMO  Investigação da relação entre o sangue de lutadores de elite de jovens do sexo masculino e as densidades de lactato salivar por meio da aplicação do método de estimativa do limiar de lactato não invasivo após a realização de exercícios periódicos de luta livre estacionários O objetivo do presente estudo foi examinar a relação entre as densidades de lactato salivar e sangue de homens jovens e de elite e a frequência cardíaca através da estimativa não invasiva do limiar de lactato após a efetivação de um determinado protocolo de exercícios periódicos baseados em lutas. Para tanto, 20 jovens lutadores de elite do sexo masculino (idade de 17 ± 2,5; altura: 178,73 ± 4,4; peso: 65,2 ± 6,4; percentual de gordura: 13,45 ± 1,2) foram incorporados ao estudo. Os sujeitos efetuaram o protocolo periódico de exercício baseado em luta livre em fases de 5 minutos, para que suas frequências cardíacas pudessem ser registradas usando um medidor de frequência cardíaca Polar. A coleta de lactato sanguíneo e salivar envolveu seis fases, incluindo: modo repouso, após aquecimento por 15 minutos e, após a realização de quatro fases do exercício de 5 minutos, nas intensidades de 60%, 70%, 80% e 90%. Amostras de lactato sanguíneo e salivar foram coletadas durante os períodos de repouso passivo de 5 minutos entre as fases do exercício. Os dados foram analisados através da aplicação do teste ANOVA com medidas repetidas e teste de correlação de Spearman ao nível de significância de 0,05. Considerando os resultados, existe diferença estatisticamente significante entre os valores de sangue e lactato salivar entre as seis fases acima mencionadas. Por outro lado, existe uma correlação aceitável entre a fase cinco e a fase seis (em intensidades de 80% e 90%) dos valores de lactato sangüíneo e salivar (P <0,05, R5-69 e P <0,05, R6-59). enquanto há também uma alta correlação evidente entre a frequência cardíaca e os níveis de lactato nas fases cinco e seis (P <0,05, R5-59 e P <0,05, R6-63). Portanto, o método de estimativa de lactato salivar poderia possivelmente ser usado como um método não invasivo em estudos de fisiologia para a determinação objetiva do limiar anaeróbio para tais protocolos de exercícios.